Protest and possibilities : civil society and coalitions for political change in Malaysia - Weiss, Meredith L. (Meredith Leigh), 1972- (Contemporary issues in Asia and the Pacific., 2006)
Protest and Possibilities explores the pursuit of political reform in Malaysia, an illiberal democracy, and contrasts coalition-building and reform processes there with those of electoral authoritarian Indonesia. The study considers the roles of civil society agents (CSAs) in promoting alternative (especially noncommunal) political norms and helping to find common ground among opposition political actors, and compares recent reformist initiatives with past political trajectories. The nature of illiberal democracy encourages a combination of contained and transgressive contention, with CSAs and political parties performing distinct but complementary roles. Enough space has been allowed over time for CSAs and political parties to accumulate coalitional capital, or the mutual trust and understanding necessary for groups to find common cause and work in coalition. In addition, shifts in political opportunities and threats encourage both CSAs and political parties to alter their strategies and thinking to take advantage of windows for change, facilitating long-term normative as well as institutional change.